Elementary Calculus - Durell, Clement v.; Robson, A. (London: G. bell and sons; ltd, 1968)
This second volume deals comprehensively with higher certificate work, and covers many of the special requirements of distinction papers. It also contains the extensions required by physics and engineering students. Certain matters, such as the validity of some results in Chapter 14, the transformation of integrals in Chapter 15, and the use of sign-conventions in Chapters 16, 17 have been treated more carefully than has been usual in elementary text-books, and there is greater precision in the statements of some of the results, both in the text and the answers, than is usually demanded of an average student.
Includes index.
ne 14/03/2018
Loan
Keywords: Calculus